2014
DOI: 10.1098/rspb.2014.0893
|View full text |Cite
|
Sign up to set email alerts
|

From ‘third pole’ to north pole: a Himalayan origin for the arctic fox

Abstract: The 'third pole' of the world is a fitting metaphor for the HimalayanTibetan Plateau, in allusion to its vast frozen terrain, rivalling the Arctic and Antarctic, at high altitude but low latitude. Living Tibetan and arctic mammals share adaptations to freezing temperatures such as long and thick winter fur in arctic muskox and Tibetan yak, and for carnivorans, a more predatory niche. Here, we report, to our knowledge, the first evolutionary link between an Early Pliocene (3.60-5.08 Myr ago) fox, Vulpes qiuzhud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“…The Himalaya, water tower of the world feeds several major river systems, sustaining one-sixth of the Earth's population downstream mainly in China, India, and Nepal [1][2][3][4]. It is one of the largest glacierized areas outside the polar regions with a total area coverage of 22,800 km 2 [5] and also regarded as the 'Third Pole' of the world [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The Himalaya, water tower of the world feeds several major river systems, sustaining one-sixth of the Earth's population downstream mainly in China, India, and Nepal [1][2][3][4]. It is one of the largest glacierized areas outside the polar regions with a total area coverage of 22,800 km 2 [5] and also regarded as the 'Third Pole' of the world [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis: p1 absent, unlike Adcrocuta; earlier occurrences of Pliocrocuta retain m1 metaconid, similar to Adcrocuta where the m1 metaconid is variably present; p3 and p4 anterior accessory cusps lingually deflected, unlike aligned cusps down the midline of the tooth in Chasmaporthetes; m1 paraconid swollen, longer than protoconid and is the same height as the protoconid, unlike in ictitheres which have higher crowned m1 protoconid showing IVPP locality ZD1208, where the presently described specimens were discovered, relative to type localities of described mammal fauna nearby, local towns and topological features: Panthera blytheae and Vulpes qiuzhudingi from ZD1001 Wang et al 2014), Chasmaporthetes gangsriensis from ZD0908 , Coelodonta thibetana from ZD0740 (Deng et al 2011) and Hipparion zandaense from ZD0918 (Deng et al 2012). ZD0609 is a screen-washed micromammal locality.…”
Section: Systematic Paleontologymentioning
confidence: 91%
“…ENM outputs are strongly affected by the study area extent; therefore, the study area delimitation must consider biogeographic features reflecting the dispersal capacity of the species and the historical species distribution (Barve et al 2011). However, as biogeographic barriers are dynamic rather than static, the study area was delimited to encompass all known historical and current occurrences of the species including all land areas inside (Hersteinsson and MacDonald 1992;Dal en et al 2007;Perini et al 2010;Wang et al 2014) (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Since the Arctic fox is adapted physically and physiologically to cold conditions (Prestrud 1991;Audet et al 2002;Wang et al 2014), and given that remains have been found in different Pleistocene deposits over most of Europe and large parts of Siberia (Chesemore 1975), it is expected that it had a wide distribution during cold stages of the Pleistocene. However, the predicted geographic range of the Arctic fox during the LGM or other cold period has not been modeled, and the magnitude of range contraction since the LGM is hence poorly understood.…”
Section: Introductionmentioning
confidence: 99%